Going Along the Direction of Trained Immunity - a Herbal Supplement for the Prevention of Respiratory Infection - Ben CL Chan; Ping-Chung Leung; William KF Cheng; Zhixiu Lin; Edwin CL Yu; Ida MT Chu; Ping Chook; Carmen YS Fong; Chun-Kwok Wong (Journal of Vaccines and Immunology - Peertechz Publications, 2020)
This is a report of a clinical attempt on the creation of an evidence-based herbal supplement for the personal protection against respiratory infection including COVID-19. The herbal supplement was derived from ancient Chinese herbal formulae. It had been proven safe and effective as a preventive agent during the 2003 SARS epidemic in Hong Kong. It was used again in this pandemic for the same purpose: offering extra personal protection for the frontline medical workers. While appreciations related to apparent preventive effects had been plentiful, a repetition of trial offered to a smaller group of 700 individuals was carried out. Apart from the need for the confirmation of safety and better quality of life, a subgroup of 33 volunteers offered to have their sera checked for immunological boosting effects as had been claimed. Results showed that the two weeks' herbal supplement did achieve a clear indication of boosted immunological defense via a macrophage orientated pathway as was indicated in the changes in chemokine activities. This effects could be understood as a demonstration of "trained immunity" process.